LIBERTÀ RELIGIOSA, SICUREZZA ALIMENTARE E HALAL DEFENSE. IN MARGINE ALLE LINEE GUIDA OSCE 2019 (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Religious freedom, food security and halal defense. In the margins of the 2019 OSCE Guidelines.Balancing the relationship between public security and religious freedom in multi-confessional societies, geopolitical events and some incidents linked to the radicalization of ideas and terrorism have recently led to a compression of religious rights, especially towards Muslims who live in no Islamic Nations. The OSCE has warned of such attitudes, highlighting how these behaviours can develop racist and xenophobic sentiments and monitoring a whole range of Islamophobia acts, through hate crimes mainly aimed at the food needs of Muslims. Thus, food safety in a religious key must be counted among human rights, and has given rise to the concept of halal defense and its standardization within the accreditation standards for halal certifications.